#### Question

Solve the following quadratic equations by factorization:

(2*x* + 3)(3*x* − 7) = 0

#### Solution

We have,

(2*x* + 3)(3*x* − 7) = 0

⇒ (2*x* + 3) = 0 or (3*x* − 7) = 0

⇒ 2x = -3 or 3x = 7

⇒ x = -3/2 or x = 7/3

Thus, x = -3/2 and x = 7/3 are two roots of the equation (2*x* + 3)(3*x* − 7) = 0

Is there an error in this question or solution?

#### APPEARS IN

Solution Solve the Following Quadratic Equations by Factorization: (2x + 3)(3x − 7) = 0 Concept: Solutions of Quadratic Equations by Factorization.